The strength properties of cement board from Payung Indonesia (Hura critefans) at 1000 kg/m3 and 1200 kg/m3 / Mohd Azmi Hussain - Hussain, Mohd Azmi (2004)
This project was carried out to knowledge about the strength properties of Cement board from Payung Indonesia. The samples of experimental board were test to determine the strength properties of the sample. The testing was performing with thickness swelling and water absorption. This testing is important to determine water absorption in cement board from Payung Indonesia. Bending strength testing has been done to measurement the strength at cement board. The result value is affected by density of the sample. The result from testing shown the cement has a density 1000 kg/m3 not achieved the standard value, but the cement board at 1200 kg/m3 achieved the standard value required. So, the high density gives the maximum result rather than the low-density give the maximum result.